Divine justice religion and the development of Chinese legal culture - Katz, Paul R. 1961- (London [u.a.] Routledge, 2009)
The development of the judicial underworld : a comparative perspective background -- The judicial continuum -- Oaths and chicken-beheading rituals -- Indictment rituals -- Trials of the insane and dressing as a criminal -- Judicial rituals in Asian colonial and immigrant history -- Judicial rituals in modern Taiwan -- Case study: the Dizang Abbey
The development of the judicial underworld -- The judicial continuum -- Oaths and chicken-beheading rituals -- Indictment rituals -- Trials of the insane and dressing as a criminal -- Judicial rituals in Asian colonial and immigrant history -- Judicial rituals in modern Taiwan -- Case study
Includes bibliographical references (p. 185-218) and index
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: Customary law -- China -- History; Religion And Law -- China -- History; Justice, Administration of -- China -- History; Rites and ceremonies -- China -- History; Religion And Law -- China; Law -- China; Jurisprudence -- China; China -- Religious life and customs -- History